2014
DOI: 10.1093/infdis/jiu605
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune Bovine Colostrum as a Novel Therapy to Combat Clostridium difficile Infection

Abstract: HBC provides an oral, cost-effective, and safe alternative to antibiotic therapy for CDI. By preserving intestinal microbiota, HBC may be more efficacious than antibiotics. Additional studies are warranted to establish HBC as a viable immunotherapeutic agent for human use against CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 53 publications
(61 reference statements)
1
46
0
1
Order By: Relevance
“…The interest in studying the biological properties of bovine colostrum is related to its rich composition in bioactive molecules including growth factors, 1‐3,18 which exert a growth‐promoting or‐inhibitory activity, depending on the target cells. Several studies have demonstrated the safety and effectiveness of bovine colostrum in the treatment of gastrointestinal disorders and in the management of nonhealing wounds 3,7,8,10,15‐17,22,31,32,55,56 . Impaired wound repair can be improved by applying a combination of exogenous growth factors, thanks to their synergistic pro‐healing action in the wounded area 57‐64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in studying the biological properties of bovine colostrum is related to its rich composition in bioactive molecules including growth factors, 1‐3,18 which exert a growth‐promoting or‐inhibitory activity, depending on the target cells. Several studies have demonstrated the safety and effectiveness of bovine colostrum in the treatment of gastrointestinal disorders and in the management of nonhealing wounds 3,7,8,10,15‐17,22,31,32,55,56 . Impaired wound repair can be improved by applying a combination of exogenous growth factors, thanks to their synergistic pro‐healing action in the wounded area 57‐64 .…”
Section: Discussionmentioning
confidence: 99%
“…Bovine colostrum provides passive immunity, protecting newborns from enteric infection, and contributes to the maturation and integrity of the gastrointestinal tract 6‐10 . There is also evidence that it is effective as an adjuvant in the treatment of diseases associated to viral and bacterial infections 3,11‐17 . The growth‐promoting and tissue repair activities of bovine colostrum are due to the rich composition of growth factors, 2,3,7,8,10,18‐23 among which: insulin‐like growth factors (IGF‐I and IGF‐II), involved in cell proliferation and differentiation 3,24,25 ; the epidermal growth factor (EGF) that stimulates gut growth in neonates and gut repair processes in adults 26,27 ; the transforming growth factor‐β (TGF‐β) that has an anti‐inflammatory and anti‐proliferative activity on epithelial cells, and promotes the healing process stimulating the epithelial cell migration at wound sites 19,28 ; the transforming growth factor‐α (TGF‐α) that plays a key role in response to injuries, stimulating gastrointestinal growth and repair, 3 and controls cell migration and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was proved to alleviate symptoms of CDI in gnotobiotic piglets without detectably affecting normal intestinal microbiota [163]. Whey protein concentrate derived from immunized cow milk was proved to be safe and well tolerated in human subjects with CDI as well [164].…”
Section: Toxin-neutralizing Agentsmentioning
confidence: 99%
“…Bacteriocins and specific antibodies are further alternatives. A hyperimmune bovine colostrum showed in a recent animal trial treatment effects against CDI without affecting the gut microbiota composition (Sponseller et al ., 2015). …”
Section: Eliminating Undesired Bacteria From the Gut Microbiomementioning
confidence: 99%
“…A hyperimmune bovine colostrum showed in a recent animal trial treatment effects against ª 2016 The Author. Microbial Biotechnology published by John Wiley & Sons Ltd and Society for Applied Microbiology, Microbial Biotechnology, 9, 553-563 CDI without affecting the gut microbiota composition (Sponseller et al, 2015).…”
Section: Bacteriophagesmentioning
confidence: 99%